PENDIDIKAN ISLAM UNTUK ANAK MENURUT IBNU QAYYIM AL-JAUZIYYAH - Nia Kurniasari (QURROTI, 2023)
Islamic education is a very important part of life. With the provision of Islamic education, the younger generation will be able to withstand various tests so that they are nurtured in faith and good deeds. Humans are born in a pure state and begin with not having any knowledge. Humans are provided by God in the form of hearing, sight and heart so that they can know and understand science. Education is the process of changing the attitudes and behavior of a person or group to mature humans through training and teaching. Ibn Qayyim Al-Jauziyah is a prominent Islamic scientist who was awarded extraordinary intelligence by Allah swt. Through his intelligence he was able to produce dozens of papers that were very useful in the fields of education, fiqh, and Sufism. Some of Ibn Qayim's works are useful in the field of Islamic education from the womb to adulthood according to the guidance of the Prophet. Through this literature research, it aims to explore scientific material in the field of children's education written by Ibn Qayyim Al-Jauziyah. The educational materials according to Ibn Qayim include faith, ruhiyah, 'athifiyyah, khulukiyah, ijtimaiyah, iradiyyah, bodily and jinsiyah education. Ibn Qayim also paid attention to the manners of an educator (murabbi) and the manners of students (mu'allim). The concept of Ibn Qayim's thought on Islamic education for early childhood is in accordance with the Qur'an and the guidance of the Prophet.